Privileged Minorities : Syrian Christianity, Gender, and Minority Rights in Postcolonial India - Thomas, Sonja (Book collections on Project MUSE., 2018)
Syrian Christians in Kerala, India, although a demographic minority, are not a subordinated community. They are caste-, race-, and class-privileged and have long benefited economically and socially from their privileged position. In this book, the author focuses on Syrian Christian women to illuminate larger questions of multiple oppressions, privilege and subordination, racialization, and religion and secularism in India. Drawing on oral histories, ethnographic interviews, and personal insights, the author employs an intersectional approach and US women of color feminist theory to interrogate the relationships between religious rights and women's rights in Kerala. By exploring how inequalities within groups shape very different experiences of religious and political movements, the author lays the groundwork for imagining new feminist solidarities across religions, castes, races, and classes.